2016
DOI: 10.1111/cen.12990
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and cardiac mass and function in men with type 1 diabetes in the Epidemiology of Diabetes Interventions and Complications Study (EDIC)

Abstract: Structured Summary Objective Low testosterone concentrations have been reported to be associated with increased risk of congestive heart failure, but the mechanisms are unclear. Our objectives was to examine the relationship between endogenous testosterone and measures of cardiac mass and function among men with type 1 diabetes. Design Secondary analysis of a prospective observational study. Participants Men (n=508) in the Epidemiology of Diabetes Interventions and Complications (EDIC) study, the observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Previous findings from non-oncology settings indicate that exogenous testosterone may also directly induce physiological cardiac myocyte hypertrophy [23]. For instance, among men with type 1 diabetes, higher total testosterone was associated with higher LV mass and volume [24], and Subramanya and colleagues [25] recently reported that after a median of 9.1 years, higher free testosterone levels were independently associated with an increase in LV mass in women and men in the Multiethnic Study of Atherosclerosis. In RCTs, testosterone treatment improved cardiac biomarkers in patients with type II diabetes [26], and reduced systemic vascular resistance and increased both cardiac output and overall exercise capacity in heart failure patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings from non-oncology settings indicate that exogenous testosterone may also directly induce physiological cardiac myocyte hypertrophy [23]. For instance, among men with type 1 diabetes, higher total testosterone was associated with higher LV mass and volume [24], and Subramanya and colleagues [25] recently reported that after a median of 9.1 years, higher free testosterone levels were independently associated with an increase in LV mass in women and men in the Multiethnic Study of Atherosclerosis. In RCTs, testosterone treatment improved cardiac biomarkers in patients with type II diabetes [26], and reduced systemic vascular resistance and increased both cardiac output and overall exercise capacity in heart failure patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…Androgen receptors are present in healthy male and female hearts, and higher free testosterone levels have been associated with elevated left ventricular muscle mass (LVM) ( 3 , 4 ). Antiandrogenic therapy in male patients with prostate cancer and heart failure was associated with lower LV septal thickness, and in male patients with type I diabetes, testosterone serum levels were associated with higher LVM ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 96%
“…Although studies report upon rates of smoking and sometimes drinking in adult patients with type 1 diabetes, [2][3][4][5][6][7] very little is known about rates of other psychoactive substance use and substance use problems in this patient population. The limited data on illicit substance use are primarily confined to nonrepresentative samples of youth or young adults with type 1 diabetes.…”
mentioning
confidence: 99%
“…5,8,9 Rates of smoking and alcohol use are usually limited to responses to single-item questions, without indication of frequencies of use or problem use. [2][3][4][5][6][7] The purpose of this study was to evaluate the frequency of use, as well as problem use, of psychoactive substances in adults with type 1 diabetes. The infrastructure and recruitment capability of the T1D Exchange (T1DX) registry was leveraged to conduct a cross-sectional, web-based self-report investigation to assess the proportions of adult participants with type 1 diabetes who report current and past smoking, drinking, and psy-choactive drug use, as well as proportions with current problematic substance use.…”
mentioning
confidence: 99%
See 1 more Smart Citation